Soil and river contamination patterns of chlordecone in a tropical volcanic catchment in the French West Indies (Guadeloupe). (May 2016) - Crabit, A.; Cattan, P.; Colin, F.; Voltz, M.
Abstract: The aim of this study was to identify primary flow paths involved in the chlordecone (CLD) river contamination and quantify the CLD fluxes to assess CLD pollution levels and duration according to a typical catchment of the banana cropping area in the French Indies (Guadeloupe): the Pérou Catchment (12 km 2 ) characterized by heavy rainfall (5686 mm year −1 ). Three sub-catchments (SC1, SC2 and SC3) were studied during the hydrological year 2009–2010: a pedological survey combined with a spatialized hydrochemical approach was conducted. The average soil concentration is higher in the Pérou Catchment (3400 μg kg −1 ) than in the entire banana cropping area in Guadeloupe (2100 μg kg −1 ). The results showed that CLD stocks in soils vary largely among soil types and farming systems: the weakest stocks are located upstream in SC1 (5 kg ha −1 ), where a majority of the area is non-cultivated; medium stocks are located in Nitisols downstream in SC3 (9 kg ha −1 ); and the greatest stocks are observed in SC2 on Andosols (12 kg ha −1 ) characterized by large farms. The annual water balance and the hydro-chemical analysis revealed that the three sub-catchments exhibited different behaviors. Pérou River contamination was high during low flows, which highlighted that contamination primarily originated from groundwater contributions. The results showed that only a small part of the catchment (SC2), contributing little to the water flow, comprises a major CLD contribution, which is in agreement with the highly contaminated andosol soils observed there. Another significant result considers that at least 50 years would be required to export the totality of the actual CLD soil stocks retained in the topsoil layer. The actual time for soil remediation will however be much longer considering (i) the necessary time for the chlordecone to percolate and be stored in the shallow aquifers and (ii) its travel time to reach the river. Highlights: Investigation of the fate of Chlordecone (CLD) in a tropical catchment. High spatial variability of CLD soil stocks over the catchment. Identification of different sources of contamination involving shallow and deep aquifers. Quantification of CLD fluxes and assessment of CLD pollution levels and duration. CLD pollution should impact the environment for centuries. Abstract : A small portion of the catchment where soils are heavily contaminated is responsible for CLD river contamination. This type of pollution should impact the environment for centuries.